The DNA Binding Domain of a Papillomavirus E2 Protein Programs a Chimeric Nuclease To Cleave Integrated Human Papillomavirus DNA in HeLa Cervical Carcinoma Cells - Horner, Stacy M. (American Society for Microbiology (ASM), 2007)
Viral DNA binding proteins that direct nucleases or other protein domains to viral DNA in lytically or latently infected cells may provide a novel approach to modulate viral gene expression or replication. Cervical carcinogenesis is initiated by high-risk human papillomavirus (HPV) infection, and viral DNA persists in the cancer cells. To test whether a DNA binding domain of a papillomavirus protein can direct a nuclease domain to cleave HPV DNA in cervical cancer cells, we fused the DNA binding domain of the bovine papillomavirus type 1 (BPV1) E2 protein to the catalytic domain of the FokI restriction endonuclease, generating a BPV1 E2-FokI chimeric nuclease (BEF). BEF introduced DNA double-strand breaks on both sides of an E2 binding site in vitro, whereas DNA binding or catalytic mutants of BEF did not. After expression of BEF in HeLa cervical carcinoma cells, we detected cleavage at E2 binding sites in the integrated HPV18 DNA in these cells and also at an E2 binding site in cellular DNA. BEF-expressing cells underwent senescence, which required the DNA binding activity of BEF, but not its nuclease activity. These results demonstrate that DNA binding domains of viral proteins can target effector molecules to cognate binding sites in virally infected cells.